Forming Health Saving Competence of the Person of Conditions of Teaching - Shepenyuk, Irina Nikolaevna (Psychological Prospects Journal, 2013)
Reform of education requires a new approach to learning, which stipulated the necessity of key competencies, which relate to: all educational, objective, professional and adaptable. In the article are investigated questions of formation health saving competence of pupils of conditions of educational process.